2020
DOI: 10.1093/pch/pxaa068.051
|View full text |Cite
|
Sign up to set email alerts
|

52 KneuroKnits: Evaluating social participation and anxiety response associated with participation in a knitting group for youth with neurological conditions (pilot study)

Abstract: Background Knitting as a creative practice has a reputation for being therapeutic. There are many programs that use crafts as a method of creating social community and reducing anxiety for youth; however, there is no existing research that demonstrates these benefits. We designed a novel study to explore the benefits of a social skills knitting group on engagement and anxiety for youth with neurodevelopmental disorders. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Through the ideological and political education of college students' mental health courses, college students can better improve their understanding of the political direction, improve their political personality, including political morality, political character, political emotion and political skills, and enable them to have noble and sound personality charm (Chen & Luo 2022;Razumkina et al 2020). At the same time, it is necessary to restrict the behaviour norms of college students, improve the moral personality of college students, and improve the pertinence and effectiveness of ideological and political education of college students' mental health courses by setting up mental health courses, organising diversified psychological education activities and strengthening psychological counselling (Brestovci et al 2021;Kapur et al 2020). Some scholars also believe that the integration of mental health education and ideological and political education of college students can stimulate the spiritual motivation of college students and improve the ideological and political system of college students (Yates et al 2020).…”
Section: The Integration Path Of Mental Health Education and College ...mentioning
confidence: 99%
“…Through the ideological and political education of college students' mental health courses, college students can better improve their understanding of the political direction, improve their political personality, including political morality, political character, political emotion and political skills, and enable them to have noble and sound personality charm (Chen & Luo 2022;Razumkina et al 2020). At the same time, it is necessary to restrict the behaviour norms of college students, improve the moral personality of college students, and improve the pertinence and effectiveness of ideological and political education of college students' mental health courses by setting up mental health courses, organising diversified psychological education activities and strengthening psychological counselling (Brestovci et al 2021;Kapur et al 2020). Some scholars also believe that the integration of mental health education and ideological and political education of college students can stimulate the spiritual motivation of college students and improve the ideological and political system of college students (Yates et al 2020).…”
Section: The Integration Path Of Mental Health Education and College ...mentioning
confidence: 99%
“…http://www.hts.org.za Open Access various psychological diseases (Kapur et al 2020). Relevant studies have shown that during the epidemic period, the prevalence of anxiety and depression increased significantly when compared with the past (Thomas et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, anxiety disorders can be divided into five types, namely phobia, claustrophobia, panic disorder, social anxiety, and generalized anxiety. In order to deal with people's anxiety, researchers investigated the effectiveness of various intervention methods [4][5][6]. Research shows that film is an effective way to relieve anxiety.…”
Section: Introductionmentioning
confidence: 99%